Synergistic Cofactor Function of Factor V and Protein S to Activated Protein C in the Inactivation of the Factor Villa – Factor IXa Complex - Shea, Lei; He, Xuhua; Dahlbäck, Björn (Thrombosis and Haemostasis, 1997)
Human factor V has been shown not only to be a precursor to procoagulant factor Va but also to express anticoagulant properties. Thus, factor V was recently found to potentiate the effect of protein S as cofactor to activated protein C (APC) in the inactivation of the factor VIIIa-factor IXa complex. The purpose of this study was to determine whether the APC-cofactor function of factor V was also expressed in the bovine protein C system and to elucidate the molecular background for the species specificity of APC. For this purpose, the effects of protein S and factor V on APC-mediated inactivation of factor VIIIa were studied using purified APC, protein S and factor V of human and bovine.origin. The factor VIIIa investigated here was part of a Xase complex (i.e. factor IXa, factor VIIIa, phospholipid and calcium) and the APC-mediated inhibition of factor VIIIa was monitored by the ability of the Xase complex to activate factor X. Synergistic APC-cofactor function of factor V and protein S was demonstrated in the bovine system. The effect of bovine APC was potentiated by bovine protein S but not by human protein S, whereas both human or bovine protein S stimulated the function of human APC. Factor V did not express species specificity in its APC-cofactor activity even though bovine factor V was more potent than its human counterpart. Recombinant human/bovine protein S chimeras were used to demonstrate that the thrombin sensitive region and first epidermal growth factor-like module of protein S determine the species specificity of the APC-protein S interaction. In conclusion, both human and bovine factor V were found to express APC-cofactor activity which depends on the presence of protein S. The species specificity of APC was shown to be caused by the interaction between APC and protein S.